PERILAKU PEDAGANG SAYUR KELILING PADA ERA PANDEMI COVID-19 DI DESA SEA DUA KECAMATAN PINELENG KABUPATEN MINAHASA - Ratuela, Andre Jufandy; Porajouw, Oktavianus; Timban, Jean Fanny Junita (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the behavior of mobile vegetable traders during the Covid-19 pandemic era in Sea Dua Village, Pineleng District, Minahasa Regency. The research was carried out from October to December 2021, which was located in Sea Dua Village, Pineleng District, Minahasa Regency. Sampling used accidental sampling and determined as many as 10 mobile vegetable traders who use motorbikes and the purpose of trading locations is in the Village of Sea Dua. The data obtained in this study are primary data by looking at the behavior of mobile vegetable traders in the era of the covid-19 pandemic. The data collection technique that will be carried out in this study is to conduct direct questions and answers to respondents based on a questionnaire (question list) that has been prepared according to research needs. The study used a qualitative descriptive method in the form of a Likert scale. In this study, the highest and lowest scores were determined. The results showed that the behavior of mobile vegetable traders during the Covid-19 pandemic era in Sea Dua Village based on the knowledge of traders about the existence of a pandemic scored (68.75%) in the good category, based on the attitude of traders during the pandemic scored (75%) in the good category, and based on the actions of the trader got a score (55%) in the bad category.